Real-time vision-aided traffic monitoring - Dagless, Eric; Ali, A.T. (Zielona Góra: Uniwersytet Zielonogórski)
Image processing systems are becoming more suitable for surveillance and traffic monitoring. The paper reports on some techniques for monitoring traffic flow on motorways, using a moving object detector operating in small windows. Traffic monitoring is demonstrated using a relaxed coincidence search technique, and successful results are reported from video of a busy complex junction layout.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka